Effect of Flour Extraction Rate on the Sensory Evaluation of Iraqi Flatbread - Alhendi, Abeer S.; Al-Shalchi, Dhafer Z.; Alsallami, Rana T.; Alobaidy, Zahraa S. (Current Nutrition & Food Science, 2021)
Background: Increasing cereal fiber consumption is a trend worldwide nowadays because of the health benefits of fiber. Increasing the flour extraction rate is a way to increase fiber consumption. Methods: Three high extraction rate flours were produced (80%, 85%, and 92%) to make Iraqi flatbread. The produced flour was obtained from a big scale technical mill (10 tons/h, Altaji mill) by changing roll adjustment or merging bran output with the flour from the production line. The bread samples were evaluated for sensory acceptability using 9-points hedonic scale for palatability, flavor, and freshness, and using the just-about-right scale for color and texture attributes for three sequencing days. Results: Significant differences for palatability, color, and flavor attributes between slices of bread produced from 80% and 92% extraction rates flours were observed. There were no significant differences between the treatments for other attributes for the first day. On the second day, there were significant differences in color attribute between 92% extraction rate flour and other treatments. While the third day, there were no significant differences between the treatments for all attributes. The results also indicated that there were no significant differences in the studied attributes within the same treatment on different days. Conclusion: Iraqi consumers preferred bread prepared from lower extraction rates compared to higher, and it is mostly because of the color factor.
Keywords: extraction rate